Textual and Visual Aids for E-learning Translation Courses - Tercedor-Sánchez, María; López-Rodríguez, Clara; Robinson, Bryan (Meta, 2005)
AbstractThe methodology of an e-learning course is based on the strategies of proactive learning, focused on the student as the key element of an approach to training in which the teacher acts as a facilitator of the learning process. Within the context of the design of a translation course in an e-learning context, the teacher must bear in mind that the student is faced with tasks that require the previous design of aids that help both in the translation process and in the acquisition of field knowledge to carry them out. Furthermore, the design should reflect the new multimedia structures that the information society has brought about.We present a series of activities generated with both visual and textual material implemented in the design of e-learning courses in audiovisual translation (subtitling and multimedia), technical and scientific translation. One of the courses is accessible through the WebCT e-learning platform, another uses the BSCWTM collaborative learning platform and the virtual classroom www.aulaint.ugr.es. The activities are intended to be of use for other subjects too, since they facilitate communication between students and act at the levels of lexical, phraseological, textual and cultural competence. Emphasis is put on the students’ self-assessment of their progress.